Neuropathogenesis in cytomegalovirus infection: indication of the mechanisms using mouse models - Tsutsui, Yoshihiro; Kosugi, Isao; Kawasaki, Hideya (Reviews in medical virology, 2005)
Cytomegalovirus (CMV) is the most frequent infectious cause of developmental brain disorders and also causes brain damage in immunocompromised individuals. Although the brain is one of the main targets of CMV infection, little is known about the neuropathogenesis of the brain disorders caused by CMV in humans because of the limitations in studying human subjects. Murine CMV (MCMV) is similar to human CMV (HCMV) in terms of genome structure, pattern of gene expressions, cell tropism and infectious dynamics. In mouse models, it has been shown that neural stem/progenitor cells are the most susceptible to CMV infection in developing brains. During brain development, lytic infection tends to occur in immature glial cells, presumably causing structural disorders of the brain. In the prolonged phase of infection, CMV preferentially infects neuronal cells. Infection of neurons may tend to become persistent by evasion of immune reactions, anti‐apoptotic effects and neuron‐specific activation of the e1‐promoter, presumably causing functional neuronal disorders. It has also been shown that CMV infection in developing brains may become latent in neural immature cells. Brain disorders may occur long after infection by reactivation of the latent infection. Copyright © 2005 John Wiley & Sons, Ltd.